DEVELOPMENT OF DAM INFRASTRUCTURE ASSESSMENT BASED ON CONDITION AND SAFETY - SARWONO PURWA JAYADI (NIM : 25015031), MUCHAMMAD
With a proper planning dan financing to maintain dam safety, those thing can make serious deterioration significantly decreased. If there’s failure in dam, these thing can make flood in downstream area of the dam so it’s have a high risk. Index Condition and Risk Assessment research was made in order to make sure dam won’t failure. Those two assessment can be combined to make an comprehensive assessment because it’s main data are visual condition of dam. With those similarity, how to develop dam assessment based on dam’s condition and safety are the main goals of this research. On these research, the development of condition assessment model based on Saguling Dam and Cirata Dam. Condition assessment aspect using Condition Index with index from 1 to 5 are used for condition assessment. Condition assessment’s components are identified from secondary data. Safety evaluation aspect are using ICOLD Modified Method. Those two assessment system were combined using Analytic Hierarchy Process (AHP) to find it’s weight for the assessment model. AHP were used to analyze AHP’s linear scale questionnaire as primary data. The main respondent were member of Dam Safety Committee (DSC) that have been evaluated Saguling Dam and Cirata Dam. These research obtain that dam components for the condition assessment are Dam Area, Dam Instrumentation, Dam Spillway, and Dam Power Waterway. Dam area consist Dam Crest, Upstream Slope, Downstream Slope, Dam Groin, Left Abutment, Right Abutment, and Dam Gallery. Dam Instrumentation consist Stand Pipe Piezometer, Surface Monument, Inclinometer, Extensometer, and Seismometer. Dam Spillway consist Control Structure, Spillway Right Wall, Spillway Left Wall, Waterway, Spillway Outlet, and Spillway Gate. Dam Power Waterway consist Headrace Tunnel, Surge Tank, Penstock, Tailrace Tunnel, and Power Waterway Gate. The dam components for the safety assessment are Instrumentation, Spilllway, Dam Crest, Dam Foundation, and Reservoir Area. The condition index analysis obtain that Saguling Dam had 4,6704 index which mean Dam Saguling is in slightly damaged. The slightly damaged mean that some components needed some repairement. While Dam Cirata had 4,7499 index which mean Dam Saguling is in slightly damaged. The slightly damaged mean that some components needed some repairement. Safety assessment analysis obtain that Dam Saguling had 49 risk index or classified as Class III (High Risk) which mean Dam Saguling had high seismic and socio-enviromental risk. While Dam Cirata had 57 risk index or clasiffied as Class III (High Risk) which mean Dam Cirata had high seismic and socio- enviromental risk. Using the model that was developed, Saguling Dam had 3,8352 index value which mean Saguling Dam have moderate defect components and high risk. While Cirata Dam had 3,8749 index value which mean Cirata Dam have moderate defect components and high risk. The model that was developed had some limitation, the limitation are the index value won’t reach 5 if the dam has high seismic risk. High seismic risk are consequent of high resevoir capacity, high potensial downstream damage, and high business risk for the owner from the effect of dam failure. The other limitations are the components that can be assessed very limited, so the assessment aren’t comprehensive enough. These limitation are the effect from difference of dam type that been used as sample.